Kedudukan Notaris Dalam Gugatan Pembatalan Akta Pengikatan Jual Beli (Studi Tentang Pihak Dalam Gugatan Pembatalan Akta autentik Pada Putusan Pengadilan Tinggi Semarang Nomor 281/Pdt/2014/PT.SMG) - Reky Anggit Kurniawan (Faculty of Law Universitas Islam Indonesia, 2022)
This study aims identify the legal basis for the panel of judges at the Semarang High Court in accepting and granting the lawsuit Number 281/Pdt/2014/PT.SMG on the cancellation of the sale and purchase agreement and to analyse the responsibility of a Notary who is not a party to the cancellation lawsuit after the deed is cancelled by the court. This is an empirical research using a sociological juridical approach and qualitative analysis. The research subjects in question were the resource persons for the High Court Judge in Semarang, the Panel of Judges examining Case Number 281/Pdt/2014/PT.SMG, and Notaries in the working area of Central Java. The results of the study conclude that first, the judge does not have the authority to attract a notary to become a party to the lawsuit, this is based on jurisprudence no. 305K/Sip/1971 and Jurisprudence No. 457K/Sip/1975. The notary is not a party to the authentic deed. The court does not have the authority to cancel the notarial deed based on Jurisprudence No. 1420K/Sip/1978 & Jurisprudence No. 702K/Sip/1973. Article 1517 of the Civil Code is the main basis for declaring that the Deed of Sale and Purchase Agreement has no legal force. Second, the Notary has no legal responsibility for the existence of an authentic deed cancellation lawsuit if the Notary is not a party to the lawsuit, the Notary only has a moral obligation to facilitate the cancellation of the deed through the issuance of a deed of cancellation at the will of the partiesKey Word: Deed Cancellation Lawsuit, Position, Notary AbstrakPenelitian ini bertujuan untuk mengetahui apa yang menjadi dasar hukum majelis hakim Pengadilan Tinggi Semarang dalam menerima dan mengabulkan gugatan Nomor 281/Pdt/2014/PT.SMG tentang pembatalan akta pengikatan jual beli dan mengetahui bagaimana tanggung jawab Notaris yang tidak turut menjadi pihak dalam gugatan pembatalan akta setelah akta tersebut dibatalkan oleh pengadilan. Jenis penelitian ini adalah penelitian empiris yang menggunakan pendekatan yuridis sosiologis dan analisis kualitatif. Subjek penelitian yang dimaksud adalah narasumber Hakim Tinggi Pengadilan Tinggi Semarang, Majelis Hakim Pemeriksa Perkara Nomor 281/Pdt/2014/PT.SMG, dan Notaris wilayah kerja Jawa Tengah. Hasil penelitian menyimpulkan bahwa Pertama, Hakim tidak mempunyai wewenang untuk menarik Notaris menjadi pihak dalam gugatan, hal ini berdasar pada Yurisprudensi No. 305K/Sip/1971 dan Yurisprudensi No. 457K/Sip/1975. Notaris bukan pihak dalam akta autentik. Pengadilan tidak mempunyai wewenang untuk membatalkan akta Notaris yang didasarkan pada Yurisprudensi No. 1420K/Sip/1978 & Yurisprudensi No. 702K/Sip/1973. Pasal 1517 KUHPerdata manjadi dasar utama untuk menyatakan Akta Pengikatan Jual Beli tidak berkekuatan hukum. Kedua, Notaris tidak memiliki tanggungjawab hukum terhadap adanya gugatan pembatalan akta autentik bilamana Notaris bukan sebagai pihak dalam gugatan, Notaris hanya memiliki kewajiban moral untuk memfasilitasi pembatalan akta melalui penerbitan akta pembatalan atas kehendak para pihak.Kata-kata Kunci: Gugatan Pembatalan Akta, Kedudukan, Notaris